1999
DOI: 10.1159/000012022
|View full text |Cite
|
Sign up to set email alerts
|

Serum Pro-Gastrin-Releasing Peptide Is a Useful Marker for Treatment Monitoring and Survival in Small-Cell Lung Cancer

Abstract: We investigated the usefulness of serum pro-gastrin-releasing peptide (Pro-GRP) as a tumor marker for diagnosis, treatment monitoring and the prediction of relapse and prognosis in patients with small-cell lung cancer (SCLC). Serum samples were obtained from 127 patients with primary lung cancer (48 patients with small-cell carcinoma, 31 with adenocarcinoma, 36 with squamous cell carcinoma and 11 with large-cell carcinoma). The cutoff levels of serum Pro-GRP and neuron-specific enolase (NSE) were set at 46 pg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 12 publications
5
25
1
2
Order By: Relevance
“…25 Serum laboratory methods more accurately evaluate the evidence of viable tumor cells, and have a complementary role to the imaging studies when macroscopic tumor disappears or residual scar remains. In SCLC, tumor markers are well correlated to the response and tumor volume, 19,21,22 as was observed with Pro GRP in the current study. Therefore, CR according to the RECIST guidelines might be more appropriate in the evaluation of patients with SCLC for PCI.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…25 Serum laboratory methods more accurately evaluate the evidence of viable tumor cells, and have a complementary role to the imaging studies when macroscopic tumor disappears or residual scar remains. In SCLC, tumor markers are well correlated to the response and tumor volume, 19,21,22 as was observed with Pro GRP in the current study. Therefore, CR according to the RECIST guidelines might be more appropriate in the evaluation of patients with SCLC for PCI.…”
Section: Discussionsupporting
confidence: 84%
“…20,21 It is reported that Pro GRP reflects tumor volume and the effect of treatment more sensitively than does NSE, and that it is useful in detecting PD because Pro GRP levels increase before disease recurrence becomes evident. 19,21,22 From the results of the current study, the elevation of Pro GRP before PCI might reflect the existence of residual viable tumor cells after a series of induction treatments, even if CR or good PR is indicated by imaging. A PCI would be recommended for patients with limited and extensive disease SCLC with CR.…”
Section: Discussionmentioning
confidence: 77%
“…In these protocols, radiation dose and time factors are crucial. Tumor markers are considered to be associated with outcome (6)(7)(8)(9)(10). In addition to these factors, we proposed that tumor size affected treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Next to imaging, smoking cessation should be actively discussed. Although plasma progastrin-releasing peptide with or without neuron-specific enolase measurements may be a useful diagnostic marker to detect early recurrence [112][113][114][115], prospective trials evaluating the benefit are lacking and therefore routine tumour marker assessment is not recommended in this setting.…”
Section: Follow-upmentioning
confidence: 99%